Current Clinical Dental Practice Guidelines and the Financial Impact of COVID-19 on Dental Care Providers - Ali, Saqib; Farooq, Imran; Abdelsalam, Maha; AlHumaid, Jehan (European Journal of Dentistry, 2020)
The novel coronavirus disease 2019 (COVID-19) has been acknowledged as a pandemic by the World Health Organization (WHO). The aim of this study was to review guidelines issued by different health regulatory bodies amid the COVID-19 outbreak and financial constraints faced by dentists globally. Relevant papers and news articles were identified in Google Scholar and PubMed. The search was made using the keywords “COVID-19,” “COVID-19 and dentistry,” and “the financial impact of COVID-19 on dentistry.” Studies and news articles published in languages other than English were excluded and a final selection of 53 relevant studies, guideline documents, and news articles were made. The outbreak of COVID-19 has affected all businesses including general dental practices, which are suffering huge financial losses as they have been advised to provide only emergency dental care. These recommendations should be appreciated as a positive step but they have caused serious financial implications for dental practices. It can be concluded that current dental practice globally is limited to the provision of emergency treatments only. This step is appreciative, but has resulted in huge financial losses sustained by dental care providers (DCPs) worldwide. The governments and health regulatory bodies of developed countries are trying to help dental practices to evolve from this troublesome situation, but there is no visible policy from the underdeveloped world that could help the DCPs to save their practices from closing down due to the financial constraints.
Keywords: COVID-19; infection; general dental practices; dentistry